1q21.1 distal copy number variants are associated with cerebral and cognitive alterations in humans - Sønderby, Ida E.; Meyer-Lindenberg, Andreas (Translational Psychiatry, 2021)
Low-frequency 1q21.1 distal deletion and duplication copy number variant (CNV) carriers are predisposed to multiple neurodevelopmental disorders, including schizophrenia, autism and intellectual disability. Human carriers display a high prevalence of micro- and macrocephaly in deletion and duplication carriers, respectively. The underlying brain structural diversity remains largely unknown. We systematically called CNVs in 38 cohorts from the large-scale ENIGMA-CNV collaboration and the UK Biobank and identified 28 1q21.1 distal deletion and 22 duplication carriers and 37,088 non-carriers (48% male) derived from 15 distinct magnetic resonance imaging scanner sites. With standardized methods, we compared subcortical and cortical brain measures (all) and cognitive performance (UK Biobank only) between carrier groups also testing for mediation of brain structure on cognition. We identified positive dosage effects of copy number on intracranial volume (ICV) and total cortical surface area, with the largest effects in frontal and cingulate cortices, and negative dosage effects on caudate and hippocampal volumes. The carriers displayed distinct cognitive deficit profiles in cognitive tasks from the UK Biobank with intermediate decreases in duplication carriers and somewhat larger in deletion carriers—the latter potentially mediated by ICV or cortical surface area. These results shed light on pathobiological mechanisms of neurodevelopmental disorders, by demonstrating gene dose effect on specific brain structures and effect on cognitive function.
For the ENIGMA-CNV working group Ida E. Sønderby, Dennis van der Meer, Clara Moreau, Tobias Kaufmann, G. Bragi Walters, Maria Ellegaard, Abdel Abdellaoui, David Ames, Katrin Amunts, Micael Andersson, Nicola J. Armstrong, Manon Bernard, Nicholas B. Blackburn, John Blangero, Dorret I. Boomsma, Henry Brodaty, Rachel M. Brouwer, Robin Bülow, Rune Bøen, Wiepke Cahn, Vince D. Calhoun, Svenja Caspers, Christopher R.K. Ching, Sven Cichon, Simone Ciufolini, Benedicto Crespo-Facorro, Joanne E. Curran, Anders M. Dale, Shareefa Dalvie, Paola Dazzan, Eco J. C. de Geus, Greig I. de Zubicaray, Sonja M.C. de Zwarte, Sylvane Desrivieres, Joanne L. Doherty, Gary Donohoe, Bogdan Draganski, Stefan Ehrlich, Else Eising, Thomas Espeseth, Kim Fejgin, Simon E. Fisher, Tormod Fladby, Oleksandr Frei, Vincent Frouin, Masaki Fukunaga, Thomas Gareau, Tian Ge, David C. Glahn, Hans J. Grabe, Nynke A. Groenewold, Ómar Gústafsson, Jan Haavik, Asta K. Haberg, Jeremy Hall, Ryota Hashimoto, Jayne Y. Hehir-Kwa, Derrek P. Hibar, Manon H.J. Hillegers, Per Hoffmann, Laurena Holleran, Avram J. Holmes, Georg Homuth, Jouke-Jan Hottenga, Hilleke E. Hulshoff Pol, Masashi Ikeda, Neda Jahanshad, Christiane Jockwitz, Stefan Johansson, Erik G. Jönsson, Niklas R. Jørgensen, Masataka Kikuchi, Emma E.M. Knowles, Kuldeep Kumar, Stephanie Le Hellard, Costin Leu, David E.J. Linden, Jingyu Liu, Arvid Lundervold, Astri Johansen Lundervold, Anne M. Maillard, Nicholas G. Martin, Sandra Martin-Brevet, Karen A. Mather, Samuel R. Mathias, Katie L. McMahon, Allan F. McRae, Sarah E. Medland, Andreas Meyer-Lindenberg, Torgeir Moberget, Claudia Modenato, Jennifer Monereo Sánchez, Derek W. Morris, Thomas W. Mühleisen, Robin M. Murray, Jacob Nielsen, Jan E. Nordvik, Lars Nyberg, Loes M. Olde Loohuis, Roel A. Ophoff, Michael J. Owen, Tomas Paus, Zdenka Pausova, Juan M. Peralta, G. Bruce Pike, Carlos Prieto, Erin B. Quinlan, Céline S. Reinbold, Tiago Reis Marques, James J.H. Rucker, Perminder S. Sachdev, Sigrid B. Sando, Peter R. Schofield, Andrew J. Schork, Gunter Schumann, Jean Shin, Elena Shumskaya, Ana I. Silva, Sanjay M. Sisodiya, Vidar M. Steen, Dan J. Stein, Lachlan T. Strike, Ikuo K. Suzuki, Christian K. Tamnes, Alexander Teumer, Anbupalam Thalamuthu, Diana Tordesillas-Gutiérrez, Anne Uhlmann, Magnus O. Ulfarsson, Dennis van ‘t Ent, Marianne B.M. van den Bree, Pierre Vanderhaeghen, Evangelos Vassos, Wei Wen, Katharina Wittfeld, Margaret J. Wright, Ingrid Agartz, Srdjan Djurovic, Lars T. Westlye, Hreinn Stefansson, Kari Stefansson, Sébastien Jacquemont, Paul M. Thompson, Ole A. Andreassen and for the ENIGMA-CNV working group
Gesehen am 20.07.2021